Um sistema de informação em uso: indo além da aceitação de tecnologia da informação - Engelbert, Ricardo (2014)
This research investigates the relationship between individuals and information technology (IT) artifacts in an organizational setting. IT artifacts are adopted by companies to be applied in their business processes in order to improve operational efficiency or even to generate a competitive advantage. Often, the IT artifacts are adopted under mandatory conditions as they are designed and implemented to support core organizational business processes. If these devices are not used, no advantage can be obtained from its adoption. Many models were created to analyze how these artifacts are accepted by individuals, and the Technology Acceptance Model (TAM) is, by far, the most discussed and replicated one in the Information Systems (IS) field. The problem is that this model, that has become a paradigm for IS researchers, has its explanatory power reduced when applied to analyze acceptance in mandatory scenarios. Often, users do not see usefulness in using a particular artifact and do not perceive ease of use in doing it, which would imply an indication of non-acceptance, but users end up using the system due to mandatory condition. Our research adopts an interpretive perspective and uses qualitative methods for data analysis to investigate the phenomenon. Based on the concepts of the Adaptive Structuration Theory (AST) and the Social Construction of Technology (SCOT), the use of case of an academic portal (the IT artifact) by professors (the users) in a Brazilian educational institution (the organization) is used as a case study to analyze this relationship. Fourteen lecturers and four others stakeholders were interviewed and secondary data from the portal developers and educational institution were collected. The results demonstrate that, even in mandatory situations, users perform adaptations on the artifact in order to better align the results to their own interests. The relationship between users and artifacts generates change in the tasks, in the artifacts and even in the users. Users define a ‘self developed information system' that encompasses the tasks, the user , the artifact provided by the organization and other artifacts that the user brings to your own system. The research found a taxonomy for adaptations performed by users when dealing with artifacts and also a typology for the ‘self-developed information systems’ based in the level of adaptation applied to the task and to the artifact.